Risk and quality management relationship of software made by professionals from the Peruvian College of Eengineers of the Lima Departmental Council - Paucar Bernardo, Diana Valeria (2021)
A critical success factor in IT project management is risk management, and part of determining a project as successful is achieving software quality. In this context, the research is based on contributing in a certain way to the management of the project to achieve success through adequate risk management based on a recognized standard. The research objective is to determine the relationship between risk management and software quality in projects carried out by professionals from the Colegio de Ingenieros del Peru, Consejo Departamental Lima. The study with non-experimental design and a correlational type; a virtual survey was carried out, in which aspects such as application of risk management processes, financial planning, motivation of the work team, training, and quality attributes of the system were considered of the projects that the respondents carried out. The results indicate that risk management has a significant relationship with software quality, so performing adequate risk management in projects ensures that the expected results are achieved and, at the same time, complies with the quality characteristics.